Adding synonyms to concepts in ontology to solve the problem of semantic heterogeneity - Herlina Jayadianti; Lukito Edi Nugroho; Paulus Insap Santosa; Wahyu Widayat (International Journal of Advances in Intelligent Informatics, 2015)
Nowadays many department (community) are thinking how to get more knowledges and metadata by linking more systems from other community. There are great challenges to make all systems organizing knowledge and sharing metadata – to make it easy searched, indexed and used in different context. In this paper we will focus on metadata in specific domain - ‘Poverty’2. Regardless of the various definitions of poverty, in this paper we will focus on managing metadata in “Poverty” with many different terms therein. Ontology Mapping is the process of relating similar concepts or relations from different sources through some equivalence relation. Mapping allows finding correspondences between the concepts of two ontologies. If two concepts correspond, then they mean the same thing or closely related things. Currently, the mapping process is regarded as a promise to solve the problem between ontologies since it attempts to find correspondences between semantically related entities that belong to different ontologies. It takes as input two ontologies, each consisting of a set of components (classes, instances, properties, rules and axioms). Based on the presented reasons, we believe that ontologies with common terms and common concepts are very important in a metadata sharing process.